Oncologic Outcomes of Patients With Sarcomatoid Carcinoma of the Hypopharynx - Dai, Liyuan; Fang, Qigen; Li, Peng; Liu, Fei; Zhang, Xu (Frontiers in Oncology, 2019)
Objectives: Sarcomatoid carcinoma (SaCa) of the hypopharynx is rare, and its clinical pathologic characteristics and prognosis remain unknown. Therefore, the study aimed to analyze the oncologic outcomes of patients with SaCa of the hypopharynx. Methods: Patients with SaCa of the hypopharynx who were surgically treated in the period from January 1985 to December 2018 were enrolled from two clinical centers. A matched pair study was also performed, and each patient with SaCa of the hypopharynx was matched with one patient with squamous cell carcinoma (SCC) of the hypopharynx. The main study endpoint was disease-specific survival (DSS). Results: A total of 62 patients (all male) were enrolled. Compared to patients with traditional SCC of the hypopharynx, patients with SaCa of the hypopharynx were older and had higher rates of perineural invasion, lymphovascular invasion and cancer cachexia. The 5-year DSS rate was 20% in patients with SaCa compared to 34% in patients in the matched group, and the difference was significant (p = 0.016). According to the univariate analysis, tumor stage, lymph node stage, disease stage, and cachexia were associated with DSS. According to the Cox model, neck lymph node metastasis and disease stage were independent predictors for worse DSS. Conclusion: The prognosis of patients with SaCa of the hypopharynx is dismal, and this type of SaCa is associated with more aggressive biological behavior than traditional SCC of the hypopharynx; neck lymph neck node metastasis and disease stage were the most important predictors of DSS.